Species-specific IL-1β is an inflammatory sensor of Seneca Valley Virus 3C Protease - Huang, Xiangyu; Zhao, Zhenchao; Zhu, Cheng; Chai, Lvye; Yan, Ya; Yuan, Ye; Wu, Lei; Li, Minjie; Jiang, Xiaohan; Wang, Haiwei; Liu, Zheng; Li, Pingwei; et al. (PLoS pathogens, 2024)
Inflammasomes play pivotal roles in inflammation by processing and promoting the secretion of IL-1β. Caspase-1 is involved in the maturation of IL-1β and IL-18, while human caspase-4 specifically processes IL-18. Recent structural studies of caspase-4 bound to Pro-IL-18 reveal the molecular basis of Pro-IL-18 activation by caspase-4. However, the mechanism of caspase-1 processing of pro-IL-1β and other IL-1β-converting enzymes remains elusive. Here, we observed that swine Pro-IL-1β (sPro-IL-1β) exists as an oligomeric precursor unlike monomeric human Pro-IL-1β (hPro-IL-1β). Interestingly, Seneca Valley Virus (SVV) 3C protease cleaves sPro-IL-1β to produce mature IL-1β, while it cleaves hPro-IL-1β but does not produce mature IL-1β in a specific manner. When the inflammasome is blocked, SVV 3C continues to activate IL-1β through direct cleavage in porcine alveolar macrophages (PAMs). Through molecular modeling and mutagenesis studies, we discovered that the pro-domain of sPro-IL-1β serves as an ’exosite’ with its hydrophobic residues docking into a positively charged 3C protease pocket, thereby directing the substrate to the active site. The cleavage of sPro-IL-1β generates a monomeric and active form of IL-1β, initiating the downstream signaling. Thus, these studies provide IL-1β is an inflammatory sensor that directly detects viral protease through an independent pathway operating in parallel with host inflammasomes.